Agronomic characteristics associated with the normalized difference vegetation index (NDVI) in the peanut crop - Zerbato, Cristiano [UNESP]; Rosalen, David Luciano [UNESP]; Furlani, Carlos Eduardo Angeli [UNESP]; Deghaid, Juliano [UNESP]; Voltarelli, Murilo Aparecido (Southern Cross Publishing, 2016)
Advances in agricultural technology have led to the development of active remote sensing equipment that can potentially estimate components of crop production; however, this assessment is still in its early stages for the peanut crop. The objective of this study was to evaluate the normalized difference vegetation index (NDVI) generated by a terrestrial sensor and its relationship with agronomic variables of peanut crops grown at different densities. The parameters evaluated were the NDVI, pod yield, mass of 100 grains, green and dry mass and vegetation cover. The study was conducted in an experimental field and used a randomized block design with plots consisting of four plant populations (86,111, 103,520, 127,603 and 141,144 plants ha-1) with six replicates per treatment. The two densest populations of peanut plants showed similar behavior among the variables analyzed, whereas the variables of vegetation cover, yield and plant population strongly correlated with the NDVI obtained by the terrestrial sensor. For the seeding rates, the higher densities (14 and 18 seeds m-1) are the most recommended because showed the highest values of productivity and vegetation cover. The results indicated that the NDVI obtained through the GreenSeeker sensor can be used to estimate productivity, vegetation cover and plant population on peanut crop. This may provide an additional tool for farmers to evaluate the potential of their culture; enabling even that agronomic measures can take effect so that this potential is improved.
Keywords: Arachis hypogaea L.; Greenseeker; Plant populations; Terrestrial remote sensing